PROTOTYPE SISTEM PENIMBANGAN OTOMATIS PADA MODEL KERNEL BULK BERBASIS ARDUINO UNO - Ahmad Mahfud; Muhammad Ali Kahfi Nasution (Fakultas Teknik Universitas Muhammadiyah Jakarta, 2023)
Kernel Bulk is a temporary shelter for kernels produced at the Palm Oil Mill, before sending process to buyers. The problem is, it is not known exactly how many production kernels have been produced and collected in Kernel Bulk. Daily kernel stock measurements are usually carried out in the Kernel Storage. which can only be done the next day when the factory has stopped processing. The Automatic Weighing System Prototype is designed to provide convenience in monitoring kernel production results at any time. It is hoped that the system will be able to provide measurement data quickly and in real time. By using the Kernel Bulk model as used in the factory, as well as the use of several sensors and controllers as system controllers. In this study, four Loadcells were used as Kernel weight measuring sensors, as well as the HX711 Module signal amplifier to send measurement data to the microcontroller. Arduino Uno R3 is embedded in this prototype as a controller that functions to read sensor measurement results and provide instructions for the next stage of measurement. The Liquid Crystal Display is embedded in the panel box, to make it easier to read the measured weight. The results showed that the automatic weight measurement system worked well, with a bulk capacity of 4.7 kg, a volume of 0.008 m3, a bulk load mass of 4.7 kg, a leg strength of 70 MPa, and an electromotor with a voltage of 220 VAC, 0.2A with a rotating output of 10 RPM. The level of accuracy of mass measurement is 93.9817%.